CHARACTERIZATION OF A LANTHANUM BROMIDE DETECTOR FOR EYE LENS DOSIMETRY AT THE CANDU NUCLEAR POWER PLANTS BASED ON DIRECT MEASUREMENTS OF THE GAMMA-RAY SPECTRA. Issue 3 (15th December 2020) - Laranjeiro, A S; Bohra, F; Byun, S H; Atanackovic, J; Hanu, A R
Abstract: Gamma-ray spectra were measured using a LaBr_3 (Ce) spectrometer during the outage periods, aiming at quantifying the gamma source term of radiation workers' exposure, at the CANDU nuclear power reactors, for the purposes of eye lens dosimetry. The spectra were measured inside the boiler rooms, of the Bruce Power and Ontario Power Generation (OPG) CANDU nuclear power plants, where workers are exposed to relatively high dose rates radiation fields during the maintenance work. Prior to measurements at the CANDU reactors, the pulse shaping parameters of the gamma spectrometer were optimised for high rates gamma fields, up to an input rates of 120 kcps, in order to accomplish a high output rate with a reasonable energy resolution. In parallel, the response of the LaBr_3 (Ce) detector was characterized by experiments and Monte Carlo simulations. The gamma spectra measured at the CANDU reactors were reported in terms of the gamma-ray fluence rate spectrum. In all measured data, ^60 Co and ^95 Nb were main contributors of the gamma fields. The measured spectra have been used to calculate the dosimetric quantities of interest: personal dose equivalents H_p (10) and H_p (0.07) and eye lens absorbed dose.